(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
Additional features of the criminal offense, depending on the law, have different significance. These signs may be provided as a necessary sign in the basic structure of the crime, as well as as a qualifying sign in the elements of mitigating, aggravating or special aggravation. Article 103 of the Criminal Code of the Republic of Uzbekistan consists of two parts, the first part of which establishes responsibility for merciless treatment of a person or continuous humiliation of his honor and dignity, causing him to commit suicide or attempt to commit suicide. In the second part of this article, for those actions: